2020
DOI: 10.1111/tpj.14647
|View full text |Cite
|
Sign up to set email alerts
|

The role of lyases, NblA and NblB proteins and bilin chromophore transfer in restructuring the cyanobacterial light‐harvesting complex

Abstract: SummaryPhycobilisomes are large light‐harvesting complexes attached to the stromal side of thylakoids in cyanobacteria and red algae. They can be remodeled or degraded in response to changing light and nutritional status. Both the core and the peripheral rods of phycobilisomes contain biliproteins. During biliprotein biosynthesis, open‐chain tetrapyrrole chromophores are attached covalently to the apoproteins by dedicated lyases. Another set of non‐bleaching (Nb) proteins has been implicated in phycobilisome d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…To further characterize the APC core of the Δ( rep3 ) mutant, we used Synechocystis Δ( cpcA/B ) mutant lacking CPC rods (Hu et al. , 2020) to prepare Δ( cpcA/B/rep3 ), the CPC‐free analog of Δ( rep3 ). Sucrose gradient ultracentrifugation revealed that most of the isolated PBSs concentrated in the H fraction of Δ( cpcA/B ) and the I fraction of Δ( cpcA/B/rep3 ) (Figure 4a,d).…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the APC core of the Δ( rep3 ) mutant, we used Synechocystis Δ( cpcA/B ) mutant lacking CPC rods (Hu et al. , 2020) to prepare Δ( cpcA/B/rep3 ), the CPC‐free analog of Δ( rep3 ). Sucrose gradient ultracentrifugation revealed that most of the isolated PBSs concentrated in the H fraction of Δ( cpcA/B ) and the I fraction of Δ( cpcA/B/rep3 ) (Figure 4a,d).…”
Section: Resultsmentioning
confidence: 99%
“…NblA targets CpcB as protease adaptor recruiting Clp protease. Our data show that NblD interacts with CpcB as well but has another function, likely in opening the tight phycobilisome structure to disrupt PC hexamers, freeing them up for tagging and degradation by the NblA-Clp system and removal of the bilin chromophores by enzymes involved in this process such as NblB(68,71).…”
mentioning
confidence: 87%
“…PNAS | 7 of 12 Discovery of a small protein factor involved in the coordinated degradation of phycobilisomes in cyanobacteria https://doi.org/10.1073/pnas.2012277118 PLANT BIOLOGY 6803 lyases, biliproteins, and NblA/B implied complex interactions between these factors and processes during phycobilisome degradation (68). NblD, a small protein, is strongly up-regulated under nitrogen starvation in Synechocystis 6803 (50) and, as shown in this study, participates in phycobilisome disassembly.…”
Section: Krauspe Et Almentioning
confidence: 99%
“…In contrast to NblA, NblB is expressed similarly in both cells facing nutrient limitation and nutrient-sufficient conditions [91], indicating another, yet unknown, layer of regulation for this protein. Interestingly, recent results show that NblA and NblB not only facilitate degradation of phycobilisomes, but also binding and rearrangement of chromophores to phycobilisomes [92]. Thus, NblA and NblB might play an important role for short-term adjustments of the photocomplexes to optimize light harvesting under changing light conditions in natural environments.…”
Section: Further Examples Of Small Protein Regulators Affecting the Amentioning
confidence: 99%